(untitled) (Surkhet Journal, 2014)
Since the establishment of the then ’College of Education’ in 1956 with a view to preparing teachers required for the nation, the students who get their any degrees in education from Tribhuvan University undergo the process of practice teaching. However, its stakeholders have not taken it as seriously as they should have taken it, which is why, it has been rather ritualistic and its quality is under scrutiny. Therefore, this paper aims to explore how practice teaching can be revamped through the perspective of the head teachers from cooperating schools. To this end, the head teachers of Surkhet Valley were invited to participate in an interaction program organized by Surkhet Campus (Education). In this discussion, majority of them maintained that both host campus and cooperating schools should take joint initiatives to provide prospective teachers, trainers, and teacher educators with enough opportunities for consolidating theoretically learned ideas and strategies through experimentation.